Use of Distal Shoe for premature loss of second temporal molar: A case report - Gutiérrez Marín DDS, Natalia (2015)
The maintenance of the temporal dentition until its natural replacement is very important, due to the fact that the primary pieces are the ones in charge to secure the permanent pieces’ space, in addition to guide the eruption process. The premature loss of temporal pieces could lead to: decrease in arch perimeter, desviation of the mid line, malocclusions, ectopic eruptions, crowding, impact and/ or extrusion of permanent pieces, abnormalities in the mucous and acquisition of parafunctional habits. If early second molars extracted, can be used as a distal shoe maintainer; which is a complicated and sensitive technique, plus it is not suitable for all patients.This case report describes the use of a distal shoe in the inferior quadrant of a 5 years old child, the technique used, advantages and disadvantages of the appliance, also monitoring for one year.